2022
DOI: 10.3390/metabo12100983
|View full text |Cite
|
Sign up to set email alerts
|

A Marked Low-Grade Inflammation and a Significant Deterioration in Metabolic Status in First-Episode Schizophrenia: A Five-Year Follow-Up Study

Abstract: The objective of this study was to evaluate how schizophrenia spectrum disorders and applied long-term (5.1 years) antipsychotic (AP) treatment affect the serum level of acylcarnitines (ACs), cytokines and metabolic biomarkers and to characterize the dynamics of inflammatory and metabolic changes in the early course of the disorder. A total of 112 adults participated in the study (54 patients with first-episode psychosis (FEP) and 58 control subjects). Biomolecule profiles were measured at the onset of first-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 88 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…Patients with schizophrenia have a pronounced metabolic inflammatory imbalance, as evidenced by the presence of increased pro-inflammatory activity and obesity with changes in the metabolism of carbohydrates, lipids, and their metabolites. 96 This study showed that adipose tissue accumulation during the disease progression and treatment with antipsychotics affects a number of key homeostatic factors by disrupting the mechanisms responsible for lipid and carbohydrate metabolism and leading to undesirable changes in cytokine and adipokine profiles. The involvement of cytokines and inflammasomes in the process of development of metabolically associated fatty liver disease, which exhibits a robust immune-inflammatory dimension, was demonstrated.…”
Section: Failure Of Inflammation Resolution Mechanismsmentioning
confidence: 96%
“…Patients with schizophrenia have a pronounced metabolic inflammatory imbalance, as evidenced by the presence of increased pro-inflammatory activity and obesity with changes in the metabolism of carbohydrates, lipids, and their metabolites. 96 This study showed that adipose tissue accumulation during the disease progression and treatment with antipsychotics affects a number of key homeostatic factors by disrupting the mechanisms responsible for lipid and carbohydrate metabolism and leading to undesirable changes in cytokine and adipokine profiles. The involvement of cytokines and inflammasomes in the process of development of metabolically associated fatty liver disease, which exhibits a robust immune-inflammatory dimension, was demonstrated.…”
Section: Failure Of Inflammation Resolution Mechanismsmentioning
confidence: 96%
“…[54][55][56][57][58][59] Moreover, the chronic use of antipsychotics and the patient's sedentary lifestyle could have led to metabolic derangements, potentially worsening the inflammatory condition. 60 Her HIV infection, although well controlled, can also exert subtle inflammatory disturbances that chronically deteriorate brain function and adds to the predisposition. 61 These factors are then precipitated into a syndromic relapse by the emergence of severe anemia.…”
Section: Anemia Cognitive Functions and The Link With Psychological I...mentioning
confidence: 99%